Complex Recanalization of Chronic Total Occluison Supported by Minimal Extracorporeal Circulation in a Patient with an Aortic Valve Bioprothesis in Extraanatomic Position - Ruben Jansen; Brigitte Bathgate; Alexander Bufe; Jan-Erik Guelker (Case Reports in Cardiology)
Percutaneous coronary intervention (PCI) of chronic total occlusion (CTO) still remains a major challenge in interventional cardiology. This case describes a complex PCI of the left main coronary artery and of a CTO of the right coronary artery using a minimal extracorporeal circulation system (MECC) in a patient with an aortic valve bioprothesis in extraanatomic position. It illustrates that complex recanalization strategies can be solved combining it with mechanical circulatory support technologies.